No association of TP53 codon 72 SNP with male infertility: a study in a Chinese population and a meta-analysis. (25th February 2015) - Chan, Ying; Jiang, Hongguo; Ma, Lan; Chen, Jinbao; Li, Dongya; Meng, Yushi; Luo, Ying; Tang, Wenru
Abstract: Genetic polymorphisms may affect human male fertility. Even though TP 53 plays a role in spermatogenesis we know little about the association of the functional polymorphism at codon 72 of TP 53 with respect to susceptibility to male infertility. We conducted a case-control study to investigate this association in a Chinese population and performed a meta-analysis in different populations to clarify this association. The single nucleotide polymorphism (SNP) of TP 53 codon 72 (rs1042522 G>C) was genotyped by PCR-RFLP in 83 Chinese male infertility patients and 401 healthy controls. Meta-analysis was performed using the data from four currently available studies. The data from our study were overlayed using the v.9.0 STATA software package. We observed no association between the TP 53 codon 72 polymorphism and male infertility ( p = 0.84, OR = 1.04, 95% CI, 0.74–1.45). Meta-analysis confirmed the case-control result that there was no significant association between the codon 72 polymorphism of TP 53 and male infertility (Pro vs. Arg; p = 0.31, OR = 0.86, 95% CI, 0.65–1.15; Pro/Pro vs. Arg-carriers; p = 0.65, OR = 0.91, 95% CI, 0.61–1.36; Pro-carriers vs. Arg/Arg: p = 0.15, OR = 0.75, 95% CI, 0.51–1.11). The data presented in this communication supports the view that the codon 72 polymorphism of TP 53 may not contribute to male infertility susceptibility in the Chinese population.